Effects of oral supplementation of probiotic strains of Lactobacillus rhamnosus and Enterococcus faecium on diarrhoea events of foals in their first weeks of life. Issue 5 (23rd May 2018) - Ströbel, Christina; Günther, Elena; Romanowski, Kristin; Büsing, Kirsten; Urubschurov, Vladimir; Zeyner, Annette
Abstract: Foal first diarrhoea is one of the most prominent problems in the early life of horses. Probiotics might have the potency to prevent or at least diminish neonatal diarrhoea. We hypothesised that the treatment of foals with probiotic strains of Lactobacillus rhamnosus and Enterococcus faecium starting early after birth and then daily over 2 weeks would prevent or mitigate foal heat diarrhoea. The influence of this probiotic treatment on diarrhoea incidence and growth and health performance of young foals was investigated. Thirty‐four foals were randomly allocated to two groups. From day 1 to 14 of life, the foals received either placebo (PG, n = 16) or the probiotic treatment (TG, n = 18). Clinical examination was performed, and the faeces consistency score (FCS, 1–5; with diarrhoea defined by ≤3) was recorded once per day in weeks 1 and 2 and once weekly in weeks 3–8 of life (WL). The body height was measured at birth and after two and eight WL. Diarrhoea occurred in the 1st WL in 19% and 61% of PG and TG foals respectively. In the 1st WL, diarrhoea lasted 0.3 ± 0.8 and 1.6 ± 1.4 days in PG and TG foals respectively. In the 2nd WL, diarrhoea occurred in 94% and 84% of PG and TG foals, respectively, and lasted for 3.0 ± 1.5 and 3.7 ± 1.6 days respectively. At least two periods of diarrhoea developed in 33% and 65% of PG and TG foals respectively. The TG foals grew slightly slower than the PG foals. The results indicated that the probiotic treatment of neonatal foals as performed in this study was not suitable to reduce diarrhoea within the first two WL, because contrary to the hypothesis, the TG foals suffered more frequently and for longer periods from diarrhoea than the PG foals.